MyOx-UCNTs modified short carbon fiber reinforced resin-based composite material and preparation method thereof

By modifying the chemical graft of the dezippered carbon nanotubes on chopped carbon fibers, the MyOx-UCNTs-CF composite material is formed, which solves the problem of insufficient mechanical properties of chopped carbon fiber composite materials and significantly improves its tensile resistance and bending strength.

CN119264478APending Publication Date: 2025-01-07QINGDAO UNIV

Patent Information

Application Number
CN202411401122.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The prior art is difficult to effectively improve the mechanical properties of chopped carbon fiber composites, especially in the formation of multi-scale reinforcement bodies on carbon nanotubes.

Method used

Chemical grafting of unzipped carbon nanotubes (MyOx-UCNTs) modified with transition metal oxide and short carbon fibers was prepared by heat pressing and curing with epoxy resin matrix to form MyOx-UCNTs-CF composite material.

Benefits of technology

The ultimate tensile and bending strength of the composite material is significantly improved, and it is about 150-250% and 180-500% higher than that of pure epoxy resin, improving the mechanical properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264478A_ABST
    Figure CN119264478A_ABST
Patent Text Reader

Abstract

The invention discloses a MyOx-UCNTs-based modified short carbon fiber reinforced resin-based composite material and a preparation method thereof, and the preparation method comprises the following steps: (1) uniformly mixing a carbon nanotube subjected to unzippering treatment with a solution containing transition metal ions to obtain a transition metal oxide modified unzippering carbon nanotube (MyOx-UCNTs), M representing elements being iron, cobalt, nickel, manganese and zinc; and (2) chemically grafting the unzipped carbon nanotube modified by the transition metal oxide to the short carbon fiber. And (3) adding the MyOx-UCNT-CF into a mixed matrix of epoxy resin and a curing agent, mechanically stirring uniformly, pouring into a hot-pressing mold, and applying pressure for curing and forming. On one hand, the surface-functionalized unzipped carbon nanotubes can be relatively uniformly grafted to the short carbon fibers; due to the unique nano structure and rich surface groups of the MyOx-UCNTs, the interface bonding effect between the short carbon fibers and a matrix can be enhanced, the applied stress can be effectively transferred, stress concentration is avoided, and therefore the mechanical performance of the composite material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of interface modification of epoxy resin-based short carbon fiber composite materials, and in particular to a method for modifying the interface of epoxy resin-based short carbon fiber composite materials. y O x -UCNTs modified short carbon fiber reinforced resin-based composite material and preparation method thereof. Background Art

[0002] In recent years, carbon fiber, as a high-strength, low-density, high-modulus fiber-reinforced material, has become an important reinforcing material in high-end application fields due to its good wear resistance, heat resistance, acid and alkali resistance. Among them, carbon fiber resin-based composite materials have gradually become the preferred materials for aerospace, wind power, marine ships, automobiles and rail transportation. In order to meet more processing requirements (injection molding, additive manufacturing, etc.), short-cut carbon fiber composite materials are in urgent need of development.

[0003] In order to accelerate the application of short-cut carbon fiber composites, improving the relevant mechanical properties of short-cut carbon fiber composites has become a key factor. Based on relevant domestic research, the interface regulation between carbon fiber and resin matrix has become a current research hotspot. Among them, carbon nanotubes, as a new type of nanomaterial, have excellent characteristics of low density, large aspect ratio, high strength and high toughness. When added in a small amount, they can significantly improve the mechanical properties of epoxy resin. Therefore, carbon nanotubes are considered to be an ideal reinforcement for composite materials, and are expected to be used to improve the interface phase and thus improve its performance.

[0004] Although surface grafted carbon nanotubes can improve the interfacial bonding properties of carbon fiber epoxy composites, the contribution of mechanical meshing to interfacial reinforcement is relatively small, and the formation of multi-scale reinforcements on carbon nanotubes is considered to be an important means to solve many problems existing in carbon fiber resin-based composites. Therefore, this method shows great potential in the field of composite material interface bonding. Therefore, the invention of a method for preparing a needle-shaped ferroferric oxide-modified unzippered carbon nanotube-modified resin-based short carbon fiber composite material has great significance in the fields of scientific research and production. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a method based on M y O x -UCNTs modified short carbon fiber reinforced resin-based composite material and its preparation method, that is, an unzippered carbon nanotube modified epoxy resin-based short carbon fiber composite material based on transition metal oxide modification and its preparation method.

[0006] The technical solution of the present invention is as follows:

[0007] A M-based y O xA method for preparing a UCNTs-modified short carbon fiber reinforced resin-based composite material, comprising the following steps:

[0008] (1) uniformly mixing the unzipped carbon nanotubes with a solution containing transition metal ions to obtain unzipped carbon nanotubes M modified with transition metal oxides; y O x -UCNTs; M represents transition metal elements;

[0009] (2) Transition metal oxide-modified unzipped carbon nanotubes were chemically grafted onto short carbon fibers to obtain M y O x -UCNT-CF;

[0010] (3)M y O x -UCNT-CF was added to the mixed matrix of epoxy resin and curing agent and mechanically stirred evenly, poured into a hot pressing mold, applied a certain pressure and cured according to a certain temperature gradient to obtain the product. y O x -UCNTs-CF mass ratio is 0.1%-20%;.

[0011] The preparation method, in the step (2), the specific method is: preparing M y O x -UCNTs grafted short carbon fiber M y O x -UCNTs-CF: Prepare 50mL DMF solution of 5wt% PEI respectively, add oxidized short carbon fiber to the above solution, the molecular weight of PEI used includes 400, 600, 800, 1200; stir well at 20-50℃ and 50-500r / min stirring speed to obtain PEI-modified short carbon fiber PEI-CF; 0.2g PEI-CF is immersed in 0.1g M y O x -uCNTs in 100ml DMF solution, ultrasonically vibrate for 1h, add 10mg HATU, react at room temperature for 1h to complete the grafting reaction, then wash with deionized water, and then vacuum dry at 70℃ for 6h. The optimized fibers are recorded as Fe 3 O 4 -UCNT-CFs.

[0012] The preparation method described above includes the following steps: 0.85 g AgNO 3 Dissolve in 500 ml of deionized water and add 13.5 g of K 2 S 2 O 4The CFs were dispersed in a mixed solution of a 70°C constant temperature water bath for oxidation under magnetic stirring for 10 min. The oxidized carbon fibers were extracted with methanol for 2 h and repeatedly washed with distilled water to remove the residual mixture on the surface of the CFs.

[0013] In the preparation method, the diameter of the CNTs selected in step (1) is 20-80 nm, and the ratio of potassium permanganate to carbon nanotubes is any one of the following ratios: 1:1, 1:2, 1:3, 1:4, 1:5.

[0014] In the preparation method, the unzipped carbon nanotubes prepared in step (1) have a nanometer size of 60-300 nm, and the optimal mass ratio of potassium permanganate to carbon nanotubes is 1:1-2.

[0015] In the preparation method, the transition metal element in step (1) is iron, cobalt, nickel or manganese.

[0016] The preparation method comprises the following steps: in step (1), the unzipped carbon nanotubes are uniformly dispersed in water by ultrasonication, a certain amount of transition metal ion solution is added, dilute ammonia water is added to adjust the pH value to about 6-10, the mixture is fully stirred and then placed in an oven at 80-100 degrees Celsius for 30 minutes, filtered and washed with a large amount of anhydrous alcohol, and then dried; the obtained precursor is then calcined at 350 degrees Celsius for 120 minutes to obtain M y O x -UCNTs;

[0017] In the preparation method, the filter membrane used for filtering and washing in step (1) can be selected from any of the following: polytetrafluoroethylene filter membrane (PTFE), nylon membrane (Nylon), polypropylene filter membrane (PP), glass microporous filter membrane, and ceramic microporous membrane, with a pore size of 0.10-0.22 μm.

[0018] In the preparation method, the solvent used in step (2) can be one of the following single solvents or 2-3 mixed solvents: acetone, DMF, tetrahydrofuran, methanol, ethanol, etc. The optimal PEI molecular weight used is 600.

[0019] In the preparation method, the average epoxy value of the epoxy resin in step (3) is 0.51 mol / g, and the curing agent used can be any one of the following: aliphatic diamines and polyamines, aromatic polyamines, other nitrogen-containing compounds and modified aliphatic amines, etc.

[0020] In the preparation method, in step (3), air bubbles are removed by vacuuming at a temperature of 50-90°C for 20-90 minutes; the curing reaction is a gradual temperature increase curing, the first stage curing temperature is 60-100°C for 1-4 hours; the second stage curing temperature is 80-140°C for 2-6 hours; the third stage curing temperature is 140-180°C for 3-6 hours. The pressure applied by the hot press is 2MPa-50MPa.

[0021] In the preparation method, the composite material prepared in step (3) is tested for mechanical properties of the composite material by a universal material testing machine. y O x -The ultimate tensile and flexural strengths of UCNTs-CF are increased by about 150-250% and 180-500% respectively compared with pure epoxy resin;.

[0022] A transition metal oxide-uCNT modified short carbon fiber reinforced resin-based composite material prepared according to any one of the methods described.

[0023] On the one hand, the present invention utilizes surface functionalized unzipped carbon nanotubes to enable them to be relatively uniformly grafted onto short carbon fibers. y O x -UCNTs' unique nanostructure and abundant surface groups can strengthen the interfacial bonding between short carbon fibers and the matrix, effectively transfer the applied stress and avoid stress concentration, thereby improving the mechanical properties of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The present invention is a flow chart of a method for preparing a transition metal oxide-modified unzippered carbon nanotube-modified resin-based short carbon fiber composite material.

[0025] Figure 2 TEM images of CNTs (a) and UCNTs (b).

[0026] Figure 3 For CNTs, UCNTs and Fe 3 O 4 -Infrared spectrum of UCNTs.

[0027] Figure 4 Fe 3 O 4 -HRTEM image of UCNTs.

[0028] Figure 5 Pure CF (a), CNTs-CF (b), UCNTs-CF (c) and Fe 3 O 4 -SEM image of UCNT-CF (d).

[0029] Figure 6 Fe 3 O 4 -UCNT-CF composite material (a) tensile stress-strain curve and (b) bending resistance line.

[0030] Figure 7 Mechanism diagram of how the “thumbnail structure” in composite materials enhances the mechanical properties of epoxy resin. DETAILED DESCRIPTION

[0031] The present invention is described in detail below in conjunction with specific embodiments.

[0032] Example 1: Preparation of unzipped carbon nanotubes (UCNTs):

[0033] First, the unzipped CNTs were prepared using the modified Hummers method. Specifically, the initial 200 mg of carbon nanotubes were dispersed in 35 mL of concentrated sulfuric acid using magnetic stirring for 10 min, and then ultrasonically dispersed at room temperature for 8 h to achieve a suspension effect. Then, 0.2 g of KMnO 4 Repeat 5 times with an interval of 10 minutes and continue stirring at 50°C for 2 hours. After the reaction is completed, the mixture is slowly poured into ice (35 mL H 2 O 2 (30%)). Then, appropriate H 2 O 2 The solution was dripped into the mixture until the gas disappeared. Finally, the obtained UCNTs were washed by centrifugation and dried in an oven at 60 °C for 12 h. Figure 2 TEM images of CNTs and UCNTs. It can be seen that the diameter of CNTs is 20-50nm, and the diameter of UCNTs is significantly larger. Compared with CNTs, the degree of agglomeration of UCNTs is reduced and the dispersion is significantly improved.

[0034] Example 2: Fe 3 O 4 - Preparation of UCNTs:

[0035] Take 50 mg of UCNTs powder and ultrasonically separate it in 120 mL of deionized water for 2 h, then add 0.2 mmol FeCl 3 , ultrasonic for 30 minutes, add dilute ammonia water to adjust the pH value to about 8, stir well and put into an oven at 80-100 degrees Celsius for 30 minutes, filter and wash with a large amount of anhydrous alcohol, and then dry. Then the obtained precursor is calcined at 350 degrees Celsius for 120 minutes to obtain Fe 3 O 4 -UCNTs;

[0036] Figure 3 Display of CNTs, UCNTs and Fe 3 O 4 -UCNTs infrared characteristic peak. It can be clearly seen that the carbon nanotubes (UCNTs and Fe 3 O 4 -UCNTs) appeared at 2300cm -1 and 3400cm -1 This fully demonstrates that the carbon nanotubes treated by unzipping have more abundant oxygen-containing groups. Figure 4 It can be seen that the nanoparticles grow evenly on the carbon nanotubes and are easy to separate by magnetic attraction, indicating that the magnetic Fe 3 O 4 -UCNTs hybrid products were successfully prepared.

[0037] Example 3: Co 3 O 4 - Preparation of UCNT:

[0038] Take 50 mg of UCNTs powder and ultrasonically separate it in 120 mL of deionized water for 2 h, then add 0.2 mmol CoCl 2 , ultrasonic for 30 minutes, add dilute ammonia water to adjust the pH value to about 80, stir well and put into an oven at 80-100 degrees Celsius for 30 minutes, filter and wash with a large amount of anhydrous alcohol, and then dry. Then the obtained precursor is calcined at 350 degrees Celsius for 120 minutes to obtain Co 3 O 4 -UCNT;

[0039] Example 4: Preparation of NiO-UCNT:

[0040] Take 50 mg of UCNTs powder and ultrasonically separate it in 120 mL of deionized water for 2 h, then add 0.2 mmol NiCl 2 , ultrasonic treatment continued for 30 minutes, diluted ammonia was added to adjust the pH value to about 80, and after being fully stirred, it was placed in an oven at 80-100 degrees Celsius for 30 minutes, filtered and washed with a large amount of anhydrous alcohol, and then dried. The obtained precursor was then calcined at 350 degrees Celsius for 120 minutes to obtain NiO-UCNT;

[0041] Example 5: MnO 2 - Preparation of UCNT:

[0042] Take 50 mg of UCNTs powder and ultrasonically separate it in 120 mL of deionized water for 2 h, then add 0.2 mmol MnCl 2, ultrasonic treatment continued for 30 minutes, diluted ammonia water was added to adjust the pH value to about 80, and after being fully stirred, it was placed in an oven at 80-100 degrees Celsius for 30 minutes, filtered and washed with a large amount of anhydrous alcohol, and then dried. The obtained precursor was then calcined at 350 degrees Celsius for 120 minutes to obtain MnO 2 -UCNT;

[0043] Example 6: Preparation of ZnO-UCNT:

[0044] Take 50 mg of UCNTs powder and ultrasonically separate it in 120 mL of deionized water for 2 h, then add 0.2 mmol ZnCl 2 , ultrasonic treatment continued for 30 minutes, diluted ammonia was added to adjust the pH value to about 80, and after being fully stirred, it was placed in an oven at 80-100 degrees Celsius for 30 minutes, filtered and washed with a large amount of anhydrous alcohol, and then dried. The obtained precursor was then calcined at 350 degrees Celsius for 120 minutes to obtain ZnO-UCNT;

[0045] Example 7: Fe 3 O 4 Preparation of UCNT-CF:

[0046] (1) 0.85 g AgNO 3 Dissolve in 500 ml of deionized water and add 13.5 g of K 2 S 2 O 4 After magnetic stirring for 10 min, the CFs were dispersed in a mixed solution of a 70°C constant temperature water bath for oxidation. The oxidized carbon fibers were extracted with methanol for 2 h and repeatedly washed with distilled water to remove the residual mixture on the surface of the CF. The oxidized short carbon fibers were added to 50 mL of DMF solution (containing 600 molecular weight PEI, accounting for 5% by weight), and fully stirred at 20-50°C and a stirring speed of 50-500 r / min to obtain PEI-modified short carbon fibers.

[0047] (2) Different carbon nanotube-based carbon fibers were prepared by chemical grafting; three portions of 0.2 g PEI-modified CF were immersed in 0.1 g CNTs, UCNTs, Fe 3 O 4 -UCNT in 100ml DMF solution, ultrasonic vibration for 1h. After adding 10mg HATU, react at room temperature for 1h to complete the grafting reaction, then wash with deionized water and then vacuum dry at 70℃ for 6h. The optimized fibers obtained are labeled as CNTs-CFs, UCNTs-CFs and Fe 3 O 4 -UCNT-CFs. Figure 5The scanning electron microscopy images show that compared with the original carbon nanotube-grafted carbon fibers, UCNTs and Fe 3 O 4 -UCNT can be grafted onto the surface of chopped carbon fibers more evenly.

[0048] Embodiment 8:

[0049] Weigh 0.4g of oxidized chopped carbon fiber, then add 2g of epoxy resin and 0.5g of curing agent and stir mechanically to make it evenly dispersed in the epoxy resin matrix. After the bubbles are exhausted by vacuum, pour it into a hot pressing mold, apply a pressure of 10Mpa and hot press and cure at a temperature gradient of 90℃ for 3h, 120℃ for 2h, and 150℃ for 2h to obtain CF-EP.

[0050] Embodiment 9:

[0051] Weigh 0.4g CNTs-CFs, then add 2g epoxy resin and 0.5g curing agent and stir mechanically to make it evenly dispersed in the epoxy resin matrix. After the bubbles are exhausted by vacuum, pour it into a hot pressing mold, apply 10Mpa pressure and hot press and cure at a temperature gradient of 90℃ for 3h, 120℃ for 2h, and 150℃ for 2h to obtain CNTs-CFs-EP. The ultimate tensile and flexural strengths are increased by about 120-170% and 180-230% respectively compared with pure epoxy resin.

[0052] Embodiment 10:

[0053] Weigh 0.4g UCNTs-CFs, then add 2g epoxy resin and 0.5g curing agent and stir mechanically to make it evenly dispersed in the epoxy resin matrix. After the bubbles are removed by vacuum, pour it into a hot pressing mold, apply 10MPa pressure and heat press and cure at a temperature gradient of 90℃ for 3h, 120℃ for 2h, and 150℃ for 2h to obtain UCNTs-CFs-EP.

[0054] Embodiment 11:

[0055] Weigh 0.4g Fe 3 O 4 -UCNTs-CFs, then add 2g epoxy resin and 0.5g curing agent to mechanically stir to make it evenly dispersed in the epoxy resin matrix. After the bubbles are removed by vacuum, pour it into a hot pressing mold, apply 10MPa pressure and heat press and cure at a temperature gradient of 90℃ for 3h, 120℃ for 2h, and 150℃ for 2h to obtain Fe 3 O 4 -UCNTs-CFs-EP. Figure 6 Table 1 and Table 2 are the tensile stress-strain curves and bending stress-strain curves of the composite materials with added resin-based short fibers and the comparison of related properties.3 O 4 -UCNTs-CFs-EP obtained the highest mechanical properties, and its ultimate tensile and flexural strengths were increased by about 150-250% and 180-500% respectively compared with those of pure epoxy resin. Figure 7 Fe 3 O 4 -Mechanism diagram of the mechanical properties of UCNTs-reinforced resin-based short fiber composites.

[0056] Table 1 Comparison of mechanical properties of short carbon fiber resin-based composites with different surface treatments

[0057] Sample name Tensile strength(MPa) Flexural strength(MPa) Pure-EP 48 80 CNTs-CFs-EP 85 230 UCNTs-CFs-EP 155 310 <![CDATA[Fe 3 O 4 -UCNTs-CFs-EP]]> 200 395

[0058] Comparative Example 1: Adding Fe from different iron sources 3 O 4 -CNTs-CFs-EP composites:

[0059] (1) Take 50 mg of UCNTs powder and ultrasonically separate it in 120 mL of deionized water for 2 h. Then add 0.2 FeCl 3 , ultrasonic for 30 minutes, add dilute ammonia water to adjust the pH value to about 80, stir well and put into an oven at 80-100 degrees Celsius for 30 minutes, filter and wash with a large amount of anhydrous alcohol, and then dry. The obtained precursor is then calcined at 350 degrees Celsius for 120 minutes to obtain Fe 3 O 4 -UCNTs, for easy distinction, are labeled as Fe 3 O 4 -UCNTs-Cl

[0060] (2) Take 50 mg of UCNTs powder and ultrasonically separate it in 120 mL of deionized water for 2 h. Then add 0.2 mmol FeSO 4 , ultrasonic for 30 minutes, add dilute ammonia water to adjust the pH value to about 80, stir well and put into an oven at 80-100 degrees Celsius for 30 minutes, filter and wash with a large amount of anhydrous alcohol, and then dry. The obtained precursor is then calcined at 350 degrees Celsius for 120 minutes to obtain Fe 3 O 4 -CNTs, for easy distinction, are labeled as Fe 3 O 4 -UCNTs-SO 4 .

[0061] (3) Take 50 mg of UCNTs powder and ultrasonically separate it in 120 mL of deionized water for 2 h. Then add 0.2 mmol Fe(NO 3 )2 , ultrasonic for 30 minutes, add dilute ammonia water to adjust the pH value to about 80, stir well and put into an oven at 80-100 degrees Celsius for 30 minutes, filter and wash with a large amount of anhydrous alcohol, and then dry. The obtained precursor is then calcined at 350 degrees Celsius for 120 minutes to obtain Fe 3 O 4 -CNTs, for easy distinction, are labeled as Fe 3 O 4 -UCNTs-NO 3 .

[0062] (4) Three portions of 0.2 g PEI-CF were immersed in a solution containing 0.1 g Fe 3 O 4 -UCNTs-Cl,Fe 3 O 4 -CNTs-SO 4 , Fe 3 O 4 -CNTs-NO 3 100ml DMF solution was added and ultrasonic vibration was performed for 1h. After adding 10mg HATU, the reaction was carried out at room temperature for 1h to complete the grafting reaction. After that, the mixture was washed with deionized water and then vacuum dried at 70℃ for 6h. They were marked as Fe 3 O 4 -UCNTs-CFs-Cl,Fe 3 O 4 -UCNTs-CFs-SO 4 , Fe 3 O 4 -UCNTs-CFs-NO 3 .

[0063] (5) Weigh three portions of 0.4 g of the above different Fe 3 O 4 -CNTs-CFs, and then 2g epoxy resin and 0.5g curing agent were added and mechanically stirred to make them evenly dispersed in the epoxy resin matrix. After the bubbles were removed by vacuum, they were poured into a hot pressing mold, and a pressure of 10MPa was applied and hot pressing and curing was performed at a temperature gradient of 90℃ for 3h, 120℃ for 2h, and 150℃ for 2h to obtain Fe 3 O 4 -CNTs-CFs-EP-Cl, Fe 3 O 4 -CNTs-CFs-EP-SO 4 , Fe 3 O 4 -CNTs-CFs-EP-NO 3 Table 2 shows the Fe3 O 4 -Comparison of mechanical properties of UCNTs-CFs-EP composites. It can be seen that Fe 3 O 4 -UCNTs-CFs-EP composite material has the highest mechanical properties, with tensile strength and flexural strength of 220MPa and 428MPa respectively, which may be due to its Fe 3 O 4 It is related to the size of the nanoparticles.

[0064] Table 2 Fe of different iron sources 3 O 4 -Comparison of mechanical properties of UCNTs-CFs-EP composites

[0065]

[0066]

[0067] Comparative Example 2: Preparation of Fe with different filler amounts 3 O 4 -UCNTs-CFs composites:

[0068] (1) Take 50 mg of UCNTs powder and ultrasonically separate it in 120 mL of deionized water for 2 h. Then add 0.2 mmol FeCl 3 and 0.1mmol FeCl 2 The sample was washed with ethanol and deionized water for several times and then dried in an oven at 50°C for 12 h to obtain Fe 3 O 4 -UCNTs.

[0069] (2) 0.2 g PEI-CF was immersed in a solution containing 0.1 g Fe 3 O 4 -CNTs in 100 ml DMF solution, ultrasonic vibration for 1 h. After adding 10 mg HATU, react at room temperature for 1 h to complete CNTs, and then vacuum dry at 70 ° C for 6 h.

[0070] (3) Take 0.02g, 0.06g, 0.16g, 0.20g, and 0.4g Fe respectively 3 O 4-UCNTs-CFs were added with 2g epoxy resin and 0.5g curing agent respectively, and mechanically stirred to make them evenly dispersed in the epoxy resin matrix. After the bubbles were removed by vacuum, they were poured into a hot pressing mold, and a pressure of 10Mpa was applied and hot pressing and curing was performed at a temperature gradient of 90℃ for 3h, 120℃ for 2h, and 150℃ for 2h to obtain Fe 3 O 4 -UCNTs-CFs-EP. From the performance comparison in Table 3, it can be seen that the higher the carbon fiber content, the higher the mechanical properties. However, when the content is too high, the mechanical properties decrease to a certain extent, which may be due to its poor dispersibility leading to poor surface wetting behavior.

[0071] Table 3 Fe content of different carbon fiber 3 O 4 -Comparison of mechanical properties of UCNTs-CFs-EP composites

[0072]

[0073]

[0074] Comparative Example 3: Epoxy resin-based chopped carbon fiber composite material without CNTs added:

[0075] Untreated chopped carbon fibers were added to 2g of epoxy resin and then 0.5g of curing agent and mechanically stirred. After the bubbles were removed by vacuum, they were poured into a hot pressing mold, and a pressure of 10MPa was applied and hot pressing and curing was performed at a temperature gradient of 90℃ for 3h, 120℃ for 2h, and 150℃ for 2h to obtain CFs-EP. Table 4 shows the important influence of short carbon fibers on epoxy resin. By adding short carbon fibers, its mechanical properties have been greatly improved.

[0076] Table 4 Comparison of mechanical properties of original epoxy resin and pure carbon fiber resin-based composites

[0077] Sample name Tensile strength(MPa) Flexural strength(MPa) EP 48 80 CFs-EP 60 150

[0078] It should be understood that those skilled in the art can make improvements or changes based on the above description, and all these improvements and changes should fall within the scope of protection of the appended claims of the present invention.

Claims

1. A method based on M y O x -UCNTs modified short carbon fiber reinforced resin-based composite material preparation method, characterized in that, The following steps are involved: (1) uniformly mixing the unzipped carbon nanotubes with a solution containing transition metal ions to obtain unzipped carbon nanotubes M modified with transition metal oxides; y O x -UCNTs; M represents transition metal elements; (2) Transition metal oxide-modified unzipped carbon nanotubes were chemically grafted onto short carbon fibers to obtain M y O x -UCNT-CF; (3)M y O x -UCNT-CF is added to the mixed matrix of epoxy resin and curing agent, mechanically stirred evenly, and bubbles are removed, poured into a hot pressing mold, a certain pressure is applied, and cured and formed according to a certain temperature gradient. y O x -UCNTs-CF mass ratio is 0.1%-20%.

2. The preparation method according to claim 1, characterized in that: The specific method of step (2) is: preparing M y O x -UCNTs grafted short carbon fiber M y O x -UCNTs-CF: Prepare 50mL DMF solution of 5wt% PEI, add oxidized short carbon fibers to the above solution, the molecular weight of the PEI used is 400, 600, 800 or 1200; fully stir at 20-50℃ and 50-500r / min to obtain PEI-modified short carbon fibers PEI-CF; immerse 0.2g PEI-CF in 0.1g M y O x -uCNTs in 100ml DMF solution, ultrasonic vibration for 1h, add 10mg HATU, react at room temperature for 1h to complete the grafting reaction, then wash with deionized water, and then vacuum dry at 70℃ for 6h. The obtained optimized fibers are recorded as Fe3O4-UCNT-CFs.

3. The preparation method according to claim 1, characterized in that: The oxidation method of short carbon fibers is as follows: 0.85 g of AgNO3 was dissolved in 500 ml of deionized water, and then 13.5 g of K2S2O4 was added and magnetically stirred for 10 min. The CFs were dispersed in the mixed solution in a 70 °C constant temperature water bath for oxidation. The oxidized carbon fibers were extracted with methanol for 2 h and repeatedly washed with distilled water to remove the residual mixture on the surface of the CF.

4. The preparation method according to claim 1, characterized in that: The unzipped carbon nanotubes prepared in step (1) have a nanometer size of 60-300 nm, and the optimal mass ratio of potassium permanganate to carbon nanotubes is 1:1-2.

5. The preparation method according to claim 1, characterized in that: The transition metal element in step (1) is: iron, cobalt, nickel or manganese.

6. The preparation method according to claim 1, characterized in that: In step (1), the unzipped carbon nanotubes are ultrasonically dispersed in water, a certain amount of transition metal ion solution is added, dilute ammonia is added to adjust the pH value to about 6-10, and after being fully stirred, they are placed in an oven at 80-100 degrees Celsius for 30 minutes, filtered and washed with a large amount of anhydrous alcohol, and then dried; the obtained precursor is then calcined at 350 degrees Celsius for 120 minutes to obtain M y O x -UCNTs.

7. The preparation method according to claim 6, characterized in that: The filter membrane used for filtering and washing in step (1) can be selected from any one of the following: polytetrafluoroethylene filter membrane (PTFE), nylon membrane (Nylon), polypropylene filter membrane (PP), glass microporous filter membrane, and ceramic microporous membrane, with a pore size of 0.10-0.22 μm.

8. The preparation method according to claim 1, characterized in that: The curing reaction in step (3) is a gradual temperature curing, wherein the curing temperature of the first stage is 60-100°C and the time is 1-4h; the curing temperature of the second stage is 80-140°C and the time is 2-6h; the curing temperature of the third stage is 140-180°C and the time is 3-6h; and the pressure applied by the hot press is 2MPa-50MPa.

9. A transition metal oxide-uCNT modified short carbon fiber reinforced resin-based composite material prepared according to any one of the preparation methods of claims 1-8.

Citation Information

Patent Citations

  • Improved silicon carbide matrix for fuel cells

    EP0155310A1

Cited By

  • Additive manufacturing composite material with high thermal conductivity and low expansion coefficient and preparation method thereof

    CN120665406A